Teaching Strategy through the Word Search Game (Revista BOEM, 2025)
This study was conducted with the aim of facilitating and providing a new approach to the teaching and learning of mathematics. It is evident that the traditional teaching model, centered on repetition and problem-solving exercises, has proven to be ineffective. In addition to extending the learning time for most students, it often results in poor academic performance and a loss of interest. In response to this issue, we propose the development of a different type of word search game—a puzzle commonly knownas the “15 Puzzle”—in which students must identify key terms. However, the true challenge lies in organizing the syllables to form the correct words. The word search game has emerged as an effective teaching and learning methodology, engaging students as active participants in the construction of knowledge within the classroom. This study seeks to explore the implementation of this educational technology as an active teaching method that encompasses relevant concepts and themes. It takes into account the student's learning process, shaped by the teacher’s knowledge and creativity, applied through the use of educational technologies. Grounded in the works of Antunes (2011), Luckesi, and Passos (1996) on creative learning and models that stimulate the investigation of educational resources, this research was developed and applied in the classroom with undergraduate mathematics students at the Federal Institute of Education, Science and Technology of Pará (IFPA), Belém Campus, in the course "Developmental Psychology of Learning," between November 22 and 27, 2021.
Keywords: learning technology; educational game; learning; creativity